The Influence of Project-Based Learning with a STEM Approach on Students' Physics Creative Thinking Skills - Ulfa Alfiana; Gunawan Gunawan; Wahyudi Wahyudi (Indonesian Journal of STEM Education, 2026)
This study aims to investigate the impact of STEM-integrated Project-Based Learning (PjBL) on Grade 10 students' creative thinking skills. A quasi-experimental method with a non-equivalent control group design was employed. The research population comprised 324 Grade 10 students at SMA Negeri 1 Lingsar during the 2025/2026 academic year. Using a purposive sampling technique, two classes were selected: Class X8 (n=36) as the experimental group and Class X2 (n=36) as the control group. The experimental group was treated with the STEM-PjBL model, while the control group followed a conventional learning model. Data were collected using an instrument consisting of seven essay items focused on renewable energy topics. The results indicated that the experimental group achieved a higher average score (74.31), categorized as "creative," compared to the control group (66.19), categorized as "moderate." Hypothesis testing using a pooled variance t-test yielded tcount = 2.44, exceeding the ttable value of 1.99 at a 5% significance level. Consequently, Ha was accepted, confirming that the STEM-integrated Project-Based Learning model significantly enhances students' creative thinking skills in physics.